2023
DOI: 10.1088/2632-2153/acc512
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive sampling for accelerating neutron diffraction-based strain mapping *

Abstract: Neutron diffraction is a useful technique for mapping residual strains in dense metal objects. The technique works by placing an object in the path of a neutron beam, measuring the diffracted signals and inferring the local lattice strain values from the measurement. In order to map the strains across the entire object, the object is stepped one position at a time in the path of the neutron beam, typically in raster order, and at each position a strain value is estimated. Typical dwell times at neutron dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This result also highlights the advantage of the GP-based approach, where a researcher could connect the GP as part of a library for dynamically driving experiments. Venkatakrishnan et al [8] demonstrated the use of GP to dynamically sample a strain field using the GPR to identify the next measurement location. A higher-level implementation of this approach could add additional control to dynamically adjust the measurement gauge Effects of the strain gradients on how the GP and Bayesian optimization select points are highlighted in Figure 6, where the selection operation identifies a higher density near the strain gradients in LTT while a more uniform grid evolves for MS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result also highlights the advantage of the GP-based approach, where a researcher could connect the GP as part of a library for dynamically driving experiments. Venkatakrishnan et al [8] demonstrated the use of GP to dynamically sample a strain field using the GPR to identify the next measurement location. A higher-level implementation of this approach could add additional control to dynamically adjust the measurement gauge Effects of the strain gradients on how the GP and Bayesian optimization select points are highlighted in Figure 6, where the selection operation identifies a higher density near the strain gradients in LTT while a more uniform grid evolves for MS.…”
Section: Discussionmentioning
confidence: 99%
“…This work uses the GPR approach presented in [ 8 ] to reconstruct the strain fields from a subset of experimental data points. GP has become a popular machine-learning technique that can infer values of unknown points on a grid from a partial set of measurements [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation